Bottom trawl fishery discards in the Black Sea coast of Turkey - CEYLAN, Y.; ŞAHİN, C. and KALAYCI, F. (Mediterranean Marine Science, 2013)
The purpose of this study is to determine the amount of bycatch and discardfish caught by bottom trawlers used in the Black Sea coasts of Turkey anddiscard changes depending on the depth. The study was conducted during theSeptember 2009 – April 2010 fishing season. Twenty-one bottom trawleroperations were sampled and the catch composition was determined. A total of 26species were caught, which included 22 species of fish, 2 species of arthropods,1 species of gastropods and 1 species of bivalves. Two of these were targetspecies (Mullusbarbatus, Merlangius merlangus), while 25 species werediscarded including trash fish and specimens below the legal size. A total of2142.76 kg of biomass was caught during the operations, of which 53.99 % bycatch.The weighted discard rate was determined as 42.06% and two different groupswere identified in discards (T1: 10-57 m, T2: 72-118 m) based on the depth. Significantdifferences were identified between these depth groups (p<0.05). It was determined that the biomass (kg h-1),the evenness index (J) (p<0.05),the average species number and the species richness (D) (p<0.01) of the discards showed significant differences, but thatthe difference between species diversity (H) was negligible. No difference wasfound (p>0.05) between theecological parameters of landings.